2022
DOI: 10.1007/s00464-022-09767-w
|View full text |Cite
|
Sign up to set email alerts
|

SX-ELLA biodegradable stent for benign oesophageal strictures: a systematic review and proportion meta-analysis

Abstract: Background This systematic review aimed to analyse the use of the SX-ELLA biodegradable stent (BDS) for benign oesophageal strictures through the assessment of clinical and technical success, differences in pre- and post-BDS insertion dysphagia scores, rates of stent migration, and safety. Methods A systematic review was reported according to PRISMA guidelines, with a prospectively registered protocol. The databases PubMed, Embase, SCOPUS, and ClinicalTria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In summary, ELLa-BDS demonstrates remarkable flexibility and biocompatibility. As previously mentioned, multiple studies have consistently confirmed the safety and efficacy of ELLa-BDS (van Boeckel et al, 2011;van Hooft et al, 2011;Hirdes et al, 2012a;McCain et al, 2016;Walter et al, 2018;Kailla et al, 2023). ELLa-BDS exhibited more promising results than PLLA-BDS, with a notably low migration rate (Dhar et al, 2009;van Boeckel et al, 2011;van Hooft et al, 2011;Yang et al, 2016).…”
Section: Pdomentioning
confidence: 57%
See 1 more Smart Citation
“…In summary, ELLa-BDS demonstrates remarkable flexibility and biocompatibility. As previously mentioned, multiple studies have consistently confirmed the safety and efficacy of ELLa-BDS (van Boeckel et al, 2011;van Hooft et al, 2011;Hirdes et al, 2012a;McCain et al, 2016;Walter et al, 2018;Kailla et al, 2023). ELLa-BDS exhibited more promising results than PLLA-BDS, with a notably low migration rate (Dhar et al, 2009;van Boeckel et al, 2011;van Hooft et al, 2011;Yang et al, 2016).…”
Section: Pdomentioning
confidence: 57%
“…In 2022, a non-randomized, single-arm prospective trial ( Yano et al, 2022 ) conducted across eight institutions provided compelling evidence that ELLa-BDS was indeed effective in treating RBES and demonstrated a satisfactory safety profile. Furthermore, a recent systematic review and proportion meta-analysis conducted by Kailla et al (2023) in 2023 demonstrated that ELLa-BDS’s high technical sophistication and moderate clinical efficacy support its use in the management of adult BES. However, further evidence is required to substantiate its advantage over alternative approaches such as endoscopic dilation.…”
Section: Materials Used In Biodegradable Esophageal Stentsmentioning
confidence: 99%